Modeling of the Policy Design to Build Public Confidence Facing Recession Issues - Rosana Eri Puspita; Iskandar; Khoirun Nisa Afina (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2024)
The condition of global economic uncertainty initiated the news that Indonesia is predicted to have the potential for recession. This study presents a model for designing policies to create public Confidence in East Java in the face of recession. The method used in this study begins with grounded theory and continues with modeling and policy simulation. Grounded theory is carried out with netnographic studies to find concepts and quantitative studies to test these concepts in the people of East Java. The netnography study was conducted by extracting sample data totaling 3,827 netizen comments using Nawala software and processed using NVIVO software. Quantitative studies are carried out by testing data collected with instruments in the form of questionnaires. The sample size amounted to 120, with respondents from East Java. Quantitative data were obtained using SPSS software to see how much influence factors affect public Confidence in East Java. Modeling is done using Powersim software, and policy simulation is done using Promethee software. The results show that low interest rates in optimistic simulations and Business as Usual (BAU) decisions can be made by Bank Indonesia (BI). The latest update in this research is that the modeling is carried out not only based on East Java's macroeconomic conditions but also on grounded theory studies in East Java community studies